Wira ekspress mobile apps as computer assisted learning in supporting cocurriculum subject - Norkhairani, Abdul Rawi; Abdullah, Ibrahim; Hasni, Hassan; Salman, Lambak; Mohd Rahim, Ariffin; Nur Auni Athirah, Mohd Nordin (2019)
The development of education in Malaysia shows positive developments from physical and spiritual aspects. The drive of human values is seen as important in shaping students who have a human value to meet the challenges ahead. Among the activities for applying this value is through the cocurriculum program. Students are encouraged to work with local and international communities to achieve the goal of developing soft skills. Generally, university students often carry out activities outside of lectures at various locations. Hence, students are exposed to some emergency situations that require them to act fast. They need to implement the initial aid measures before actual help arrives. Among the most common emergencies during physical activity outside the classroom are falling due to broken, electric shock, venomous bites, and food poisoning. This emergency can also occur if they are at home or at the hostels. Prototype named Hero Express is an application that can be stored on a student's mobile phone that can be used when the emergency occurs as an initial rescue step before the ambulance arrives. This app has several modules, namely Kecemasan (broken, insect bites, etc.), Hati-hati (refers to some areas in the home to be taken into account by the students) as well as Uji Diri (grasp the level of student understanding of emergency measures). It can help students make early references in case of anxiety towards them. The co-curriculum student feedback is very positive on the usability of this app to guide them during emergency situations.